On the types species of the New World dung beetle genus Canthidium Erichson, 1847 (Coleoptera: Scarabaeidae: Scarabaeinae), with an annotated checklist of species - Cupello, Mario (Zootaxa, 2018)
In this work, it is explained why previous authors who considered that Canthidium lentum Erichson, 1947 (Coleoptera: Scarabaeidae: Scarabaeinae) was fixed as the type species of Canthidium Erichson, 1847 in Robert Lucas’ 1920 catalogue of Coleoptera genera were mistaken. Instead, the first authors to designate a type species for Canthidium were Martínez et al. in 1964, who designated C. thalassinum Erichson, 1847. Since both species are currently placed in different subgenera, the subgeneric classication must change: Eucanthidium Halffter & Martínez, 1986 is a new junior synonym of Canthidium, while the subgenus previously considered to be Canthidium (Canthidium) is changed to Canthidium (Neocanthidium) Martínez et al., 1964 based on the revalidation of the latter name. A checklist containing information on the type locality, type material, synonymy, and distribution of all the 172 valid species included in the genus (72 in the nominotypical subgenus, 69 in Neocanthidium, and 31 as incertae sedis) is presented, as well as a review of the taxonomic history of Canthidium and the new synonymy between C. (C.) ardens Bates, 1887 and Canthidium ardens mutatum Bates, 1887.